PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP EARNING RESPONSE COEFFICIENT (ERC) DENGAN GOOD CORPORATE GOVERNANCE (GCG) SEBAGAI VARIABEL MODERASI - OKTAVIA LESTARI, RISKI Oktavia (Jurnal Akuntansi AKUNESA, 2014)
This study examines Corporate Social Responsibility (CSR) disclosure to Earning Response Coefficient (ERC) with Good Corporate Governance (GCG) as a moderating variable proxied by managerial ownership, institutional ownership, the proportion of independent board and audit committee. Samples from this study are companies listed on the Indonesia Stock Exchange in 2008-2012 after eligible purposive sampling so that amounts to 45 companies. The data analysis technique used in this study is hypothesis testing with multiple linear regression method.The results showed that the variables of corporate social responsibility disclosure, managerial ownership and audit committee does not effect to earning response coefficient. Variables such as institutional ownership and the proportion of independent board effect to earning response coefficient. While good corporate governance has no effect on corporate social responsibility disclosure relationship with earning response coefficient.Keywords: earning response coefficient, corporate social responsibility, good corporate governance